2021
DOI: 10.3390/jpm11121376
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Real-World Long-Term Outcomes of People with CF Homozygous for the F508del Mutation Treated with CFTR Modulators

Abstract: The clinical response to cystic fibrosis transmembrane conductance regulator (CFTR) modulators is variable within people with cystic fibrosis (pwCF) homozygous for the F508del mutation. The prediction of clinical effect in individual patients would be useful to target therapy to those who would benefit from it. A multicenter observational cohort study was conducted including 97 pwCF (F508del/F508del), who started lumacaftor/ivacaftor (LUM/IVA) treatment before June 2018. In order to assess the associations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…Most studies reported a moderate change from baseline ppFEV1 [13,14] and a moderate change in ppFEV1 decline after one [16,17] or two years [18] of follow-up. The discrepancy with a different recently published study that focused on predictors of long-term clinical outcomes using encounter-based ppFEV1 measurements [19] might be explained by the inclusion of annual best ppFEV1 measurements in the NCFR. Annual best measurements may provide a better estimation of long-term trends, as this reduces the impact of measurement variability over time compared to multiple repeated measurements.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Most studies reported a moderate change from baseline ppFEV1 [13,14] and a moderate change in ppFEV1 decline after one [16,17] or two years [18] of follow-up. The discrepancy with a different recently published study that focused on predictors of long-term clinical outcomes using encounter-based ppFEV1 measurements [19] might be explained by the inclusion of annual best ppFEV1 measurements in the NCFR. Annual best measurements may provide a better estimation of long-term trends, as this reduces the impact of measurement variability over time compared to multiple repeated measurements.…”
Section: Discussioncontrasting
confidence: 76%
“…Nevertheless, similar differences were reported in the PROGRESS trial, showing an increasing BMI trend in treated pwCF and matched registry controls, whereas BMI Z-score and weight-for-age trend improved after LUM/IVA initiation compared to a decline in matched registry controls [6]. Moreover, LUM/IVA and TEZ/IVA might induce a short-term improvement of pulmonary exacerbations [13,14] and reduce the use of IV antibiotics in the first year after treatment initiation in pwCF above 12 years of age, but this improvement was not sustained in the subsequent years [18,19]. This could indicate that the benefit of dual CFTR modulators on severe pulmonary exacerbations diminishes on the long-term, but it could also be related to a decreasing long-term adherence to modulators or to a reduced prescription or adherence to other co-medication such as dornase alpha, hypertonic saline and inhaled antibiotics in a real-life setting, The contrast between short-and long-term changes in this study also illustrates that traditional short-term clinical endpoints such as ppFEV1 might not always be the best measures to capture treatment benefits.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Elexacaftor is a CFTR corrector that operates at a different binding location on the CFTR protein than tezacaftor to improve the CFTR protein's functioning at the cell surface [ 15 ]. When administered as a combination, Trikafta enhances the function of the Phe508del mutant CFTR protein on the cell surface, resulting in greater chloride ion transport and amelioration of symptoms [ 9 , 16 , 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…In patients homozygous for Phe508del mutations, elexacaftor-tezacaftor-ivacaftor revealed no serious adverse events and no consequences that led to cessation when compared to tezacaftor-ivacaftor. Both experimental groups experienced similar adverse effects, which were mostly resolved by the end of the four-week study [ 17 , 25 ].…”
Section: Reviewmentioning
confidence: 99%